2019
DOI: 10.1101/828343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Plausible Accelerating Function of Intermediate States in Cancer Metastasis

Abstract: Epithelial-to-mesenchymal transition (EMT) is a fundamental cellular process and plays an essential role in development, tissue regeneration, and cancer metastasis. Interestingly, EMT is not a binary process but instead proceeds with multiple partial intermediate states. However, the functions of these intermediate states are not fully understood. Here, we focus on a general question about how the number of partial EMT states affects cell transformation. First, by fitting a hidden Markov model of EMT with expe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…The regulators of pEMT are also associated with cell-cycle regulation (Goetz et al, 2020;Denisov and Perelmuter, 2018). For instance, hypoxia can elevate TGFB1 levels (Topalovski et al, 2016), a transcription factor known to induce complete EMT in epithelial cells (Hao et al, 2019).…”
Section: Review Pemt and Cell Cycle Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulators of pEMT are also associated with cell-cycle regulation (Goetz et al, 2020;Denisov and Perelmuter, 2018). For instance, hypoxia can elevate TGFB1 levels (Topalovski et al, 2016), a transcription factor known to induce complete EMT in epithelial cells (Hao et al, 2019).…”
Section: Review Pemt and Cell Cycle Regulationmentioning
confidence: 99%
“…Multiple pEMT states and phenotypes have been identified in various cell lines, and during metastasis in vivo and pEMT cancer cells are more prone to metastatic outgrowths (Donnenberg et al, 2018;Goetz et al, 2020;Karacosta et al, 2019;Pastushenko et al, 2018;Schliekelman et al, 2015;Stylianou et al, 2019). In a systematic mathematical analysis, Goetz et al (Goetz et al, 2020) concluded that more the number of intermediate states, the more chances to metastasize. The simulations showed that by stabilizing one intermediate state, cells can be trapped for a much longer slowing down complete EMT.…”
Section: Metastasismentioning
confidence: 99%
“…A hallmark of regulatory networks enabling phenotypic switching in cancer cell populations is multi-stability, i.e., the ability of isogenic cells to reversibly acquire diverse phenotypes [ 5 , 11 , 12 , 57 , 58 , 59 , 60 , 61 ], as reported earlier also for bacterial [ 62 ] and viral [ 63 ] populations. Multi-stability can enable ‘spontaneous’ switching among cell phenotypes (different attractors in the Waddington’s landscape) due to biological noise (that can operate at multiple levels including transcriptional or conformational [ 64 , 65 ]), and thus facilitate non-genetic heterogeneity [ 8 , 66 ].…”
Section: Discussionmentioning
confidence: 83%
“…Our analysis reveals that ICS plays the crucial role in not only interchanging information with both pure epithelial and mesenchymal states, but also communicating with other cells in ICSs during EMT. Previously, the role of ICSs has been studied for tumor metastasis ( Jolly et al, 2015 ) and analyzed through the emergent dynamical properties such as signal adaptation, noise attenuation, and population transition ( Ta et al, 2016 ; Sha et al, 2019 ; Goetz et al, 2020 ). Taken together, the EMT cell lineage models with ICS-mediated feedback through cell–cell communications ( Lander et al, 2009 ; Lo et al, 2009 ) could be further developed to explore the non-linear effects on different cell populations ( Jia W. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%